2022
DOI: 10.1186/s12962-022-00368-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cross-regional medical treatment on total medical expenses, medical insurance payments, and out-of-pocket expenses of patients with malignant tumors in Chinese low-income areas

Abstract: Background In recent years, due to the increasing number of cross-regional medical patients, countries around the world have issued a series of policies or regulations to reduce their out-of-pocket burden. In this context, this study intended to explore the impact of the Spatio-temporal characteristics of cross-regional medical treatment on total medical expenses, medical insurance payments, and out-of-pocket expenses of patients with malignant tumors in low-income areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Respondents who had health insurance were more likely to have a home first-aid kit than those who paid for their own medical expenses. It has been found that differences in medical expenses payment methods reflect differences in the medical care level received [ 14 ]. Respondents without health insurance were likely to be financially disadvantaged and have relatively low incomes, therefore being less likely to have a home first-aid kit.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents who had health insurance were more likely to have a home first-aid kit than those who paid for their own medical expenses. It has been found that differences in medical expenses payment methods reflect differences in the medical care level received [ 14 ]. Respondents without health insurance were likely to be financially disadvantaged and have relatively low incomes, therefore being less likely to have a home first-aid kit.…”
Section: Discussionmentioning
confidence: 99%
“…The uneven geographical distribution of healthcare resources is a major factor driving the increase in the number of patients opting for medical services in various locations ( 4 ). The scope of insurance coverage varies between insured and uninsured areas, with the insured areas encompassing entities such as countries, cities, and other administrative regions ( 5 ). For instance, within the European Union (EU), each member state typically has its own insurance coverage zone.…”
Section: Introductionmentioning
confidence: 99%
“…In China, cross-regional treatment of patients usually refers to the medical behavior of the population insured by basic medical insurance and whose medical treatment location does not coincide with where they are insured ( 6 , 7 ), including three levels: cross-county, cross-city and cross-province ( 8 ).Many countries such as Germany, the United Kingdom and Japan, have established government/compulsory health insurance coverage covering nearly the whole population ( 9 ). Similarly, China has also established a basic medical insurance scheme covering more than 95% of the population ( 10 ), including two main categories: Urban Employees’ Basic Medical Insurance (UEBMI) and Urban and Rural Residents’ Basic Medical Insurance (URRBMI).…”
Section: Introductionmentioning
confidence: 99%
“…Only several studies were identified researching the utilization of cross-regional hospitalization services. On the one hand, they focused on analyzing the utilization of cross-regional hospitalization services by patients diagnosed with a specific disease such as tumor ( 6 , 8 , 12 ), rare diseases ( 13 ), and non-emergency hip arthroplasty ( 14 ); on the other hand, they were only restricted to one certain aspect of cross-regional hospitalization service utilization, such as the choice of medical institution level ( 14 , 15 ), hospitalization expenses and deductibles ( 16 ). However, rare research was found analyzing the utilization of cross-regional hospitalization services for patients insured by basic medical insurance from a more comprehensive perspective.…”
Section: Introductionmentioning
confidence: 99%